Публічна служба в правоохоронній сфері та правоохоронна функція держави - Комірчий, П. О. (My University, 2018)
Статтю присвячено спробі сформулювати універсальне визначення поняття «публічна служба в правоохоронній сфері», беручи до уваги сутнісний зміст правоохоронної функції держави, яку ця публічна служба реалізує. Особливу увагу приділено критичному аналізу наукових підходів до розуміння понять «правоохоронна функція держави», визначено їх переваги та недоліки. Наголошено на безумовному зв’язку правоохоронної функції держави з функціонуванням публічної служби в правоохоронній сфері також дозволяє її розглядати у концептуальному аспекті, а саме в якості особливого соціального і правового феномену, без належного функціонування якого неможливе існування сучасної держави, а також панування права у суспільстві та державі загалом. На основі з’ясованого сутнісного змісту правоохоронної функції держави та публічної служби в Україні здійснюється концептуалізація публічної служби в правоохоронній сфері як особливого соціально-правового явища. Найбільш повно ця публічна служба відбивається саме у діяльності державних службовців, котрі перебувають на службі в правоохоронних органах України – безпосередньо реалізуючи правоохоронну функцію держави. Зроблено висновок, що в інституціональному контексті публічна служба у правоохоронній сфері охоплює усіх публічних службовців, котрі, виконуючи свої посадові обов’язки, впливають на правоохоронну сферу, охороняючи правопорядок, права і свободи людини та громадянина. Визначено, що публічна служба у правоохоронній сфері України – це адміністративно-правовий інститут підгалузі публічної служби, що в практичній дійсності об’єктивується в особливій та безперервній, неупередженій професійній діяльності громадян України, котрі володіють належним рівнем службової правосуб’єктності, на посадах в правоохоронних органах України з приводу реалізації в інтересах держави та суспільства посадових завдань щодо належного підтримання функціонування цих державних органів та виконання функцій цих органів на підставі, в межах повноважень та у спосіб, що передбачені Конституцією та законами України. The article is devoted to the attempt to formulate a universal definition of the concept "public service in the law-enforcement sphere", taking into account the substantive content of the law-enforcement function of the state, which this public service implements. Particular attention is paid to the critical analysis of scientific approaches to understanding the concepts of "law enforcement function of the state", their advantages and disadvantages are determined. The unconditional connection between the law-enforcement function of the state and the functioning of the public service in the law-enforcement sphere also emphasizes the conceptual aspect, namely, as a special social and legal phenomenon, without proper functioning of which the impossibility of the existence of a modern state, as well as the rule of law in society and the state as a whole. On the basis of the clarified substantive content of the law-enforcement function of the state and public service in Ukraine, the conceptualization of public service in the law-enforcement sphere is carried out as a special social-legal phenomenon. This public service is most fully reflected in the activities of civil servants who are serving in law enforcement agencies of Ukraine - directly implementing the law enforcement function of the state. It is concluded that in the institutional context public service in the law-enforcement sphere covers all public servants who, while performing their duties, influence the lawenforcement sphere, protecting the rule of law, human and citizens' rights and freedoms. It has been determined that public service in the law-enforcement sphere of Ukraine is an administrative-legal institution in the sub-sector of the public service, which in practice is objectified in the special and continuous, unbiased professional activity of Ukrainian citizens who have an appropriate level of official legal personality, in positions in law-enforcement the authorities of Ukraine concerning the implementation of official tasks in the interests of the state and society regarding the proper maintenance of the functioning of these state bodies and the fulfillment of the functions of these bodies on the pond, within the powers and in the manner envisaged by the Constitution and laws of Ukraine.
Public service in the law enforcement sphere and the law enforcement function of the state
Keywords: правоохоронна функція держави; публічна служба в правоохоронній сфері; публічна служба; публічний службовець; функції держави; functions of the state; law-enforcement function of the state; public servant; public service in the law-enforcement area; public service